2017
DOI: 10.2196/resprot.6047
|View full text |Cite
|
Sign up to set email alerts
|

Using Text Messaging in Long-Term Arthroplasty Follow-Up: A Pilot Study

Abstract: BackgroundPatient-reported outcome measures (PROMs) and mobile technology have the potential to change the way patients are monitored following joint replacement surgery.ObjectiveThe aim of this study was to determine the feasibility of text messaging to record PROMs in long-term follow-up of hip and knee arthroplasty. Our participants were 17 patients 2-years-plus post hip or knee arthroplasty attending clinic with a mobile telephone number on record.MethodsA simple PROM (Oswestry Very Short Form) was texted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…2 Similarly, Blocker et al utilized text messaging to follow arthroplasty patients at greater than two years follow-up and concluded that text messaging is viable avenue for following patients long-term. 4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Similarly, Blocker et al utilized text messaging to follow arthroplasty patients at greater than two years follow-up and concluded that text messaging is viable avenue for following patients long-term. 4…”
Section: Discussionmentioning
confidence: 99%
“…Anthony et al 2 evaluated text messaging for delivery of the patient questionnaires in the early postoperative period and reported >85% follow-up at virtually no cost. Similarly, Blocker et al 4 utilized text messaging to follow patients undergoing arthroplasty with >2 years of follow-up and concluded that text messaging is a viable avenue for following patients long-term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 17 studies used written reminders such as email, SMS or push notifications. 21,26,27,[29][30][31][32][33]39,42,44,49,54,55,60,65,69 Two studies used telephone reminders, and one reminded people when they arrived at the clinic. 48 Nonparticipation and dropout rates.…”
Section: Included Studiesmentioning
confidence: 99%
“…Used less than five sessions 3 Withdrew after randomization BLOCKER ET AL. 29 11 Did not complete 53 Did not engage BROCHMANN N. E AL. 30…”
mentioning
confidence: 99%